(3MGTjI GdHGLhQi Ydi GdSeQbfOis - (3EHQGgje Hf eMeO GdHGLhQis; (3GdSeQbfOjs ((3YeQ Hf GdSjO eMeO OjH GdSbYGf GdHjQhJi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi NUfG HGdHjGf hHYO ajbhd EHQGgje GdHGLhQi bO SCdfi HYV GdENhGf cJGHI RcjI Ydi GdebOeI GdeSeGI HGdSeQbfOjI , JHjf eQGOgG hJcTa dKGegG s
(3BNQgG (B:s
(3hgPG BNQ eG jSQg Gddg JYGdi Ydi gPG GdeJf GdTQja , hCHQC Edi Gdehdi GdNHjQ GddWja hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdHdGZIs